2015
DOI: 10.1074/mcp.m114.042812
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry of Human Leukocyte Antigen Class I Peptidomes Reveals Strong Effects of Protein Abundance and Turnover on Antigen Presentation

Abstract: HLA class I molecules reflect the health state of cells to cytotoxic T cells by presenting a repertoire of endogenously derived peptides. However, the extent to which the proteome shapes the peptidome is still largely unknown. Here we present a high-throughput mass-spectrometry-based workflow that allows stringent and accurate identification of thousands of such peptides and direct determination of binding motifs. Applying the workflow to seven cancer cell lines and primary cells, yielded more than 22,000 uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

47
535
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 398 publications
(586 citation statements)
references
References 69 publications
(113 reference statements)
47
535
3
1
Order By: Relevance
“…By integrating exome sequencing, MHC peptide ligand prediction algorithms and targeted MS, Gubin et al recently identified tumor-specific mutant MHC class I peptides as targets of this form of immunotherapy (88). Proteogenomics approaches (139, 140) using DDA MS were also recently used for the identification of mutant as well as polymorphic MHC class I peptides (5,51,(141)(142)(143)(144). Notably, the detection of tumor-specific mutant MHC peptides has not been achieved yet using DIA MS.…”
Section: Identification and Quantification Of Mhc-associated Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…By integrating exome sequencing, MHC peptide ligand prediction algorithms and targeted MS, Gubin et al recently identified tumor-specific mutant MHC class I peptides as targets of this form of immunotherapy (88). Proteogenomics approaches (139, 140) using DDA MS were also recently used for the identification of mutant as well as polymorphic MHC class I peptides (5,51,(141)(142)(143)(144). Notably, the detection of tumor-specific mutant MHC peptides has not been achieved yet using DIA MS.…”
Section: Identification and Quantification Of Mhc-associated Peptidesmentioning
confidence: 99%
“…1, middle panel). In fact, this method can be used for the isolation of both class I and class II MHC peptides from a range of biological sources such as cell lines, primary tissues and plasma (36,(51)(52)(53). Moreover, up to ϳ90% of immunopurified peptides were reported to be specific for the MHC molecules (51,54).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, MS/MS spectrum generation and acquisition is even more important in immunopeptidomics as compared to other sample types due to the very diverse physical chemical properties of these endogenous peptides 25. Thanks to tremendous technological development in the MS/MS field over the last decade, large‐scale MHC‐class I and MHC‐class II immunopeptidome analyses have taken off in recent years,6, 26, 27 thus drastically increasing the availability of immunopeptidome datasets.…”
Section: Lc‐ms/ms‐based Detection Of Immunopeptidomesmentioning
confidence: 99%
“…Ideally, this can be achieved using TCR-like antibodies specific for every HLA/HBV-epitope complex [43,44] but the diversity of complexes makes this approach unfeasible [45] . Peptide elution and mass spectrometry strategies [46] might seem possible, but such techniques is highly specialized and complex, and at the moment restricted primarily to academic research and not clinical application. As a compromise, the detection of HBV proteins, DNA or mRNA would suffice with the assumption that antigen processing and epitope presentation occurs as expected.…”
Section: Practical Considerations For Safe and Effective T Cell Immunmentioning
confidence: 99%